1998
DOI: 10.1006/inco.1997.2687
|View full text |Cite
|
Sign up to set email alerts
|

Error-Free and Best-Fit Extensions of Partially Defined Boolean Functions

Abstract: In this paper, we address a fundamental problem related to the induction of Boolean logic: Given a set of data, represented as a set of binary "true n-vectors" (or "positive examples") and a set of "false n-vectors" (or "negative examples"), we establish a Boolean function (or an extension) f , so that f is true (resp., false) in every given true (resp., false) vector. We shall further require that such an extension belongs to a certain specified class of functions, e.g., class of positive functions, class of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 19 publications
(45 reference statements)
0
41
0
Order By: Relevance
“…There may be no such solution, particularly if there are errors in the data leading to logical inconsistencies, or if the class of functions considered is restricted for practical or theoretical reasons. If so, we may then proceed by analogy with statistical modeling, accepting a best-fit solution that minimizes the number of misclassifications within the data, as in Boros, Ibaraki, and Makino (1998). When consistent solutions exist they will almost certainly not be unique.…”
Section: Inference Methods -Logical Consistencymentioning
confidence: 99%
“…There may be no such solution, particularly if there are errors in the data leading to logical inconsistencies, or if the class of functions considered is restricted for practical or theoretical reasons. If so, we may then proceed by analogy with statistical modeling, accepting a best-fit solution that minimizes the number of misclassifications within the data, as in Boros, Ibaraki, and Makino (1998). When consistent solutions exist they will almost certainly not be unique.…”
Section: Inference Methods -Logical Consistencymentioning
confidence: 99%
“…Proof : The property is a simple extension of binary case (see [6]), and we therefore leave the details to the reader.…”
Section: Positive Functionsmentioning
confidence: 99%
“…The binary case of this problem has been already studied (e.g. in [6]) and it would not be hard to generalize the result in a straightforward way to the ternary case. So let us now look at the case with missing bits and the rules for their feasible replacements.…”
Section: Introductionmentioning
confidence: 99%
“…Early work in this area was targeted at binary domains. Recent work has extended this target to include numeric predictor attributes by using a process known as "binarization" (Boros et al 1997). Consider the example from Boros et al (1997) shown in Table 1.…”
Section: Building Classifiers Using Nonlinearmentioning
confidence: 99%